Longitudinal patterns of legal socialization in first-generation immigrants, second-generation immigrants, and native-born serious youthful offenders - Piquero, Alex R. (Crime & delinquency, 2016)
It is now well documented that the view that immigrants commit more crime than native-born persons is not supported by empirical research. Yet, the knowledge base is limited in our understanding of the criminological frameworks that may distinguish these groups and, in part, lead to divergent offending patterns. We use the legal socialization framework to understand potential differences along with data from the Pathways to Desistance to assess differences in legal socialization perceptions between first-generation immigrants, second-generation immigrants, and native-born serious youthful offenders. Results show that, compared with second-generation and native-born youth, first-generation youth tend to have more positive views toward the law, less cynical attitudes toward the legal system, and report more social costs associated with punishment.